Meta-Analysis of The Effect of Problem Based Learning Model on Understanding Physics Concepts of High School Students - Tomi Putra Wijaya; Anisa Triwijaya; Frennadito Menix; Desnita Desnita (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
The purpose of this research was to determine the effect of problem based learning on the understanding of high school students' concepts. The meta-analysis, which was conducted by summarizing several research articles on the effect of problem based learning on physics learning, was also carried out on students' understanding of concepts in physics learning obtained from articles published between 2015 and 2020. In particular, this research obtained an effect size (ES) =1.005 (high category). The research was conducted by grouping 20 articles into two categories, namely based on the material unit, and based on the approach used. Based on the material unit, there are 15 articles that were analyzed by effect size (ES) and obtained an effect of 0.82 with a high category with a percentage of 54.5%. The material with the greatest influence is temperature and heat with ES = 1.78, while the grouping based on the approach used there are 5 articles that were analyzed with the results of the effect size (ES) analysis of 1.19 with a high category with a percentage of 60%. The approach that has the most influence on PBL is HOTS with ES= 3.02. From the results of this study, it can be seen that the PBL model has a significant effect on physics learning. The hope of this research is that it can be a reference in reviewing the application of PBL in learning in Indonesia.